Effects of Career Development and Competencies on Social Affairs: Employee Performance as Mediating Variable - Andi Muh. Irfan; Jabir Hamzah; Muhammad Ismail (Hasanuddin Economics and Business Review, 2023)
This study aims to know how great the influence of career development, motivation work, and competence on employee performance as well as the impact on the Social Affairs Agency of South Sulawesi Province. Method analysis used is analysis path. The research results show that the development of a career and competence in a way simultaneous is very influential in social assistance services. However, partially, competency does not influence social assistance services, while employee performance partially has a strong relationship with social assistance services. A combination of development career, competency, and performance employee is a strong unity that affects social assistance services. The results of the indirect effect test using Sobel Test calculations have proven that there is a positive and significant indirect effect on career and competency development, through employee performance regarding social assistance services. This indicates that performance employees are capable of mediating completely (full mediation) between career development and competency towards improving social assistance services at the Social Affairs Agency of South Sulawesi Province.